Entrepreneurship Education Strategy in Higher Education in ASEAN: Competitive Intelligence and Readiness to Change - Trilaksono, Teddy; Marchalina, Leonis; Sasmoko, Sasmoko; Indrianti, Yasinta; Yusak, Nurul Aqilah Binti Muhammad (APMBA (Asia Pacific Management and Business Application), 2022)
This study presents empirical evidence on the condition of entrepreneurship education from universities in ASEAN countries facing the ASEAN Economic Community (AEC). Survey data was obtained from 174 lecturers in five ASEAN countries and was analysed using a normality test with PP-plot and a linearity test. The urge of this study is to integrate the managerial and marketing skills in the entrepreneurship education curriculum in higher education in the face of a rapidly changing global business condition. The government must ensure that higher education institution (HEI) in the country creates a business ecosystem in the internal campus environment or encourages students to seek a business ecosystem outside the HEI and creates mentors from lecturers to accompany these students. Theoretically, this study has expanded the theory of entrepreneurship education, competitive intelligence, and readiness to change in the context of ASEAN institutions. In practice, this study helps in preparing an entrepreneurship education agenda for both leaders and educators who influence entrepreneurship education to become more effective, so that their students can apply their entrepreneurship skills after they graduate.